Summer Lake Destratification Phenomenon: A Peculiar Deep Lake on the Tibetan Plateau - Su, Rongmingzhu; Xie, Zhipeng; Ma, Weiqiang; Ma, Yaoming; Wang, Binbin; Hu, Wei; Su, Zhongbo (Frontiers in Earth Science, 2022)
Lake water temperature and the related thermal structure influence not only the provision of ecosystem services in lacustrine environments, but also the interactions with regional climate. However, continuous lake temperature monitoring across the Tibetan Plateau is sparse, limiting our understanding of lake thermal and mixing dynamics, and hindering the verification of modeling results in this region. Based on in-situ water temperature and meteorological observations, this study revealed a special summer destratification phenomenon of a deep alpine lake, Langa Co. The results indicate that Langa Co is a discontinuous cold polymictic lake, which becomes completely mixed and reaches a homogeneous water temperature frequently during spring and autumn. Further, the intermittent periods of stratification in summer only last a few days, which is rare for such a deep lake. As an example of a discontinuous cold polymictic lake that contrasts with the typical dimictic pattern of alpine lakes, studies of Langa Co help to gain insights into lake thermal processes and thermoregulation mechanisms and establish a reference for lake model evaluation and parameterization on the Tibetan Plateau.